Los Vieneses Österreichische Kabarettkünstler*innen im Spannungsfeld von Austrofaschismus, Nationalsozialismus und Franquismus - Finkenstedt, Verena (2023)
The story of the Vieneses illuminates the unique transfer of interwar Jewish Viennese entertainment culture to Francoist Spain and its decades-long influence on Barcelona's revue theatre and the beginning of Spanish national television.